2006
DOI: 10.1128/jb.00006-06
|View full text |Cite
|
Sign up to set email alerts
|

Gene Involved in Transcriptional Activation of the hrp Regulatory Gene hrpG in Xanthomonas oryzae pv. oryzae

Abstract: A novel regulatory gene, trh, which is involved in hrp gene expression, is identified in the plant pathogen Xanthomonas oryzae pv. oryzae. In the trh mutant, expression of HrpG, which is a key regulator for hrp gene expression, is reduced both under the in vitro hrp-inducing condition and in planta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…A recent paper reports that a putative transcriptional regulator gene, named trh (transcriptional regulator for hrp), is involved in expression of HrpG in X. oryzae pv. oryzae (74). Putting these results together, the orphan regulator HrpG might function as part of multiple regulatory systems rather than interacting with a single cognate HK that senses external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper reports that a putative transcriptional regulator gene, named trh (transcriptional regulator for hrp), is involved in expression of HrpG in X. oryzae pv. oryzae (74). Putting these results together, the orphan regulator HrpG might function as part of multiple regulatory systems rather than interacting with a single cognate HK that senses external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, we previously found that another H-NS protein, XrvB, negatively regulates hrpG expression (25). In addition, the GntR family transcriptional regulator Trh and the two-component signal transduction system PhoP/PhoQ have also been reported to be involved in the transcriptional regulation of hrpG (26,27). Thus, not only the phosphorylation of the first key hrp regulator, HrpG, followed by the activation of the second key hrp regulator, HrpX, but also the transcriptional regulation of hrpG are likely to be important, although the transcriptional regulation of hrpG by the regulators that have been identified so far is probably all indirect.…”
mentioning
confidence: 99%
“…oryzae (17,18). A novel regulatory gene, trh, was identified as a positive regulator of HrpG both under in vitro hrp-inducing conditions and in planta (52). Also, HrpX was reported to be regulated by the expression of some other effectors.…”
Section: Discussionmentioning
confidence: 99%
“…(7,11,12,15,50,52,56,57). It was reported that hrpG itself was shown to be regulated by other regulators.…”
Section: Discussionmentioning
confidence: 99%